Debt Management Performance Assessment : Lesotho - World Bank (World Bank, Washington, DC, 2020)
From September 21 to September 28, 2012, a joint World Bank and Macroeconomic and Financial Management Institute of Eastern and Southern Africa (MEFMI) team visited Maseru, Lesotho to undertake a comprehensive assessment of debt management functions. The team used the Debt Management Performance Assessment (DeMPA) tool. In the governance and strategy area, there is a clear delegation to the minister of finance for borrowing and issuance of guarantees, but the mechanisms for coordination are not well developed. The coordination with macroeconomic policies generally meets the minimum requirements even though there is no clear separation with monetary operations. Cash management is not actively conducted despite very large cash balances in the Central Bank of Lesotho (CBL). There is no cash flow forecasting and no interest is earned on government cash balances. Strengths have been identified in the operational risk management area. There is a duality requirement for recording of both domestic and external loans. The debt records are not complete as domestic guarantees generally are not recorded. The treasury bonds and bills are recorded by the Public Debt Management Division (PDMD) with an average lag of three months.